Pengembangan Booklet Tumbuhan Paku di Taman Hutan Raya Sultan Thaha Syaifuddin Sebagai Bahan Pengayaan Mata Kuliah Taksonomi Tumbuhan : The Development of Booklet on the Subject Matter of Ferns (Pteridophytes) from the Sultan Thaha Syaifuddin's Forest Park as Enrichment Material of Plant Taxonomy Course - Muswita Muswita; Upik Yelianti; Lia Kusuma; Amita Intan (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
T The research aims to develop and determine the feasibility of Ferns booklets in Tahura STS. This type of research is Research and Development research using ADDIE learning design models. The booklet that was developed contains 42 types of Ferns that grow in Tahura STS, consisting of 14 types of epipitic Ferns and 28 types of terrestrial Ferns. The booklet that was developed contains scientific names, pictures, classifications and descriptions of ferns that grow in Tahura STS. Validation of media experts was carried out twice with a final score of 85.71% with the category